2015
DOI: 10.1007/s10162-015-0512-1
|View full text |Cite
|
Sign up to set email alerts
|

Perilymph Kinetics of FITC-Dextran Reveals Homeostasis Dominated by the Cochlear Aqueduct and Cerebrospinal Fluid

Abstract: Understanding how drugs are distributed in perilymph following local applications is important as local drug therapies are increasingly used to treat disorders of the inner ear. The potential contribution of cerebrospinal fluid (CSF) entry to perilymph homeostasis has been controversial for over half a century, largely due to artifactual contamination of collected perilymph samples with CSF. Measures of perilymph flow and of drug distribution following round window niche applications have both suggested a slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 28 publications
(22 reference statements)
2
44
1
Order By: Relevance
“…It has been shown that drug delivery in rodent cochlea is much more effective when injected through the semicircular canal than through the round window, because rodents have a large cochlear aqueduct, which is located at the base of the cochlea, next to the round window. 37,38 The AAV8-whirlin delivered through the round window may be diluted by cerebrospinal fluid from the cochlear aqueduct, or it may escape through the cochlear aqueduct, which decreases its concentration and limits its ability to infect the entire cochlea. 38 When AAV8-whirlin gene therapy was delivered through the posterior semicircular canal, the average IHC stereocilia lengths in the eight whirler mice that showed hearing recovery were much longer than in our previous study in which AAV8-whirlin was injected through the round window.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that drug delivery in rodent cochlea is much more effective when injected through the semicircular canal than through the round window, because rodents have a large cochlear aqueduct, which is located at the base of the cochlea, next to the round window. 37,38 The AAV8-whirlin delivered through the round window may be diluted by cerebrospinal fluid from the cochlear aqueduct, or it may escape through the cochlear aqueduct, which decreases its concentration and limits its ability to infect the entire cochlea. 38 When AAV8-whirlin gene therapy was delivered through the posterior semicircular canal, the average IHC stereocilia lengths in the eight whirler mice that showed hearing recovery were much longer than in our previous study in which AAV8-whirlin was injected through the round window.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 The AAV8-whirlin delivered through the round window may be diluted by cerebrospinal fluid from the cochlear aqueduct, or it may escape through the cochlear aqueduct, which decreases its concentration and limits its ability to infect the entire cochlea. 38 When AAV8-whirlin gene therapy was delivered through the posterior semicircular canal, the average IHC stereocilia lengths in the eight whirler mice that showed hearing recovery were much longer than in our previous study in which AAV8-whirlin was injected through the round window. 14 This is likely due to the significantly higher number of hair cells with whirlin expression achieved in the present study (the AAV8-whirlin used in this study is the same as in our previous study).…”
Section: Discussionmentioning
confidence: 99%
“…In the guinea pig, cerebrospinal fluid (CSF) entry into the scala tympani through the cochlear aqueduct has been described to have a diluting effect on substances delivered through the round window. This dilution has been theorized to derive both from entry of CSF into the scala tympani and from loss of drug into the CSF space (24), with CSF entering at a very slow rate in a sealed, normal cochlea (24,25). This likely contributes to the slow, apically-directed flow within the normal guinea pig cochlea, measured to be approximately 1.6 nL/min (25).…”
Section: Discussionmentioning
confidence: 99%
“…Constant-rate injections, which were not used, would have yielded reduced flow rate as scala tympani cross section widens. Dilution of solution concentration from mixture with cerebrospinal fluid (CSF) that enters through cochlear aqueduct is one of several reasons why the common procedure of round window niche applications cannot treat the entire cochlear length (Salt et al 2015). In contrast to drug delivery at the cochlear base, apical injections avoid dilutions even at the lower range of injection rates (i.e., 25 nl/min) which are close to the measured sustained volume of cerebrospinal fluid entry of ~30 nl/min through the cochlear aqueduct (cf.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to drug delivery at the cochlear base, apical injections avoid dilutions even at the lower range of injection rates (i.e., 25 nl/min) which are close to the measured sustained volume of cerebrospinal fluid entry of ~30 nl/min through the cochlear aqueduct (cf. Salt & DeMott 1998, Salt et al 2015). Thus, from the start of the injection thereafter, the entry of cerebrospinal fluid at the base will be suppressed.…”
Section: Methodsmentioning
confidence: 99%